Problematizing the limits of personal responsibility. On a Talmudic reading of Levinas - Medina Delgadillo, Jorge (2025)
The concept of “infinite responsibility” is central to the ethics of Emmanuel Levinas. This expression synthesizes both his phenomenological intuitions and his theological tradition. Although it is recurrent in his work, the use of “infinite” poses challenges, both due to its metaphysical and scientific implications and its difficult comprehension in everyday language. This paper will analyze and problematize the Talmudic reading “The Damages Caused by Fire,” which paradigmatically illustrates the incommensurability of responsibility, a key element in Levinasian ethics. The justification for delving into a Talmudic reading may be susceptible to criticism for its religious character and, under a superficial reading, lack philosophical rigor; however, in Levinas’s philosophy, the biblical and religious tradition is so prevalent that it often merges with the philosophical, since, due to the very methodology of our author, the philosophical and, above all, the pre-philosophical (the foundation of the philosophical) do not have a definitive difference from the religious.